Implications of the Melamchi water supply project for the Kathmandu Valley groundwater system - Thapa, Bhesh Raj (IWA Publishing, 2019)
To meet the demand deficit in Kathmandu Valley, the Government of Nepal has planned to supply an additional 510 million liters per day (mld) of water by implementing the Melamchi Water Supply Project (MWSP) in the near future. In this study, we aim to assess the spatial distribution of groundwater availability and pumping under five scenarios for before and after the implementation of the MWSP using a numerical groundwater flow model. The data on water demand, supply infrastructure, changes in hydraulic head, groundwater pumping rates, and aquifer characteristics were analyzed. Results showed that groundwater pumping from individual wells ranges from 0.0018 to 2.8 mld and the average hydraulic head declined from 2.57 m below ground level (bgl) (0.23 m/year) to 21.58 m bgl (1.96 m/year). Model simulations showed that changes in average hydraulic head ranged from þ2.83 m to þ5.48 m at various stages of the MWSP implementation, and 2.97 m for increased pumping rates with no implementation of the MWSP. Regulation in pumping such as monetary instruments (groundwater pricing) on the use of groundwater along with appropriate metering and monitoring of pumping amounts depending on the availability of new and existing public water supply could be interventions in the near future.